Sources and upstream pathways of the densest overflow water in the Nordic Seas - Huang, Jie; Pickart, Robert S.; Huang, Rui Xin; Lin, Peigen; Brakstad, Ailin; Xu, Fanghua (Nature Communications, 2020)
Overflow water from the Nordic Seas comprises the deepest limb of the Atlantic Meridional Overturning Circulation, yet questions remain as to where it is ventilated and how it reaches the Greenland-Scotland Ridge. Here we use historical hydrographic data from 2005-2015, together with satellite altimeter data, to elucidate the source regions of the Denmark Strait and Faroe Bank Channel overflows and the pathways feeding these respective sills. A recently-developed metric is used to calculate how similar two water parcels are, based on potential density and potential spicity. This reveals that the interior of the Greenland Sea gyre is the primary wintertime source of the densest portion of both overflows. After subducting, the water progresses southward along several ridge systems towards the Greenland-Scotland Ridge. Kinematic evidence supports the inferred pathways. Extending the calculation back to the 1980s reveals that the ventilation occurred previously along the periphery of the Greenland Sea gyre. publishedVersion